Administrative sanctions procedure and reasoning of sanctions decisions - Alfaro-Alvarado, Alberto (2024)
The object of this paper focuses on the study of the reasoning of sanctions decisions provided by the Public Administration. We consider that it is necessary to address it given that currently there is still ambiguity about what we call reasoning. This is because the reasoning is approached from different perspectives that only generate indeterminacy about it. The legal system has not provided sufficient tools to determine this situation and is limited to treating the reasoning as a requirement, without providing elements to comply with it. The jurisprudence has not responded to this need either. Thus, it has been established that the reasoning does not require a detailed exposition of the reasons for the decision and that is sufficient with a simple and concise exposition of the reasons for the decision. In these lines we will ask ourselves what we mean by reasoning, also, why it is important and we will address whether the current standard in terms of reasoning in sanctions decisions provided by the public administration is satisfactory and if it is necessary to change something for a adequate compliance with the demands that derive from it.